Role of nitric oxide in gastric injury induced by hemorrhagic shock in rats - DENİZBAŞI ALTINOK, ARZU; YEGEN, BERRAK; YEGEN, ŞEVKET CUMHUR (KARGER, 2000)
The aim of this study was to investigate the effect of nitric oxide (NO) on the gastric injury induced by hemorrhagic shock. Hemorrhagic shock was created by withdrawing 3 ml blood/200 g body weight of the rats. Before the hemorrhage, N-G-nitro-L-arginine methyl ester (L-NAME, 10 mg/kg i.v. bolus), D-NAME (10 mg/kg i.v. bolus), or L-arginine (100 mg/kg i.v. bolus and 10 mg/kg/min infusion) + L-NAME were administered. At the end of the 1-hour hypovolemic shock period, histological analysis, gastric ulcer index, gastric myeloperoxidase (MPO) activity, and gastric protein oxidation (PO) levels were determined. In histological analysis a destructive effect of L-NAME (NO synthase inhibitor) was demonstrated. L-NAME treatment increased gastric MPO activity, L-arginine reversed this effect and D-NAME had no effect. Tissue PO activity was found to be increased in L-NAME-treated rats; L-arginine treatment reversed this activity. It is concluded that gastric barrier function is altered after hemorrhagic shock, and L-arginine (NO precursor) can prevent mucosal injury in the stomach. This effect of NO may be on gastric blood flow and can be mediated by tissue neutrophils. Copyright (C) 2000 S. Karger AG, Basel.
Keywords: nitric oxide; hemorrhagic shock; gastric damage; gastroprotection; lesion index; myeoloperoxidase activity; protein oxidation; DYSFUNCTION; DAMAGE; ISCHEMIA/REPERFUSION; PROTECTION; LESIONS; MUCOSA; CELLS